2020
DOI: 10.1002/ijc.33049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of Chinese R‐CHOP treated DLBCL patients: Identifying a high‐risk subgroup

Abstract: Diffuse large B‐cell lymphoma (DLBCL) is a clinically aggressive and heterogenous disease. Although most patients can be cured by immunochemotherapy, 30% to 40% patient will ultimately develop relapsed or refractory disease. Here, we investigated the molecular landscapes of patients with diverse responses to R‐CHOP. We performed capture‐based targeted sequencing on baseline samples of 105 DLBCL patients using a panel consisting of 112 lymphoma‐related genes. Subsequently, 81 treatment‐naïve patients with measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…TP53 mutations have been shown to be significantly associated with poor overall survival in DLBCL [ 38 , 39 ]. Clipson A et al [ 40 ] also found the significant association of TP53 mutation with poor overall survival in DLBCL with MYC translocation.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutations have been shown to be significantly associated with poor overall survival in DLBCL [ 38 , 39 ]. Clipson A et al [ 40 ] also found the significant association of TP53 mutation with poor overall survival in DLBCL with MYC translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Driven by the purpose of identifying genetic high-risk subtypes, most patients in that series presented with advanced-stage and high-risk disease according to the revised international prognostic index (R-IPI; part of the study has been published). 25 Retrospectively selected from that cohort, patients harboring TP53 mutations were enrolled in the present study. Clinical data were collected and analyzed: sex, age, Ann Arbor stage, Eastern Cooperative Oncology Group performance status, extranodal involvement, B symptoms, lactate dehydrogenase (LDH), bulky disease, R-IPI, first-line treatment, salvage treatment, response to treatment, and survival.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17][18][19] In DLBCL, TP53 mutation has been identified as an unfavorable prognostic factor for patients under a CHOP or R-CHOP treatment regimen. 12,[20][21][22][23][24][25] In a study of 102 DLBCL patients, the CR rate was significantly higher in patients missing TP53 mut. 25 The prognostic impact of TP53 mut was further investigated in a study with 506 de novo DLBCL patients, and the results showed TP53 mut was an independent predictor of OS and progression-free survival (PFS) in patients treated with an R-CHOP regimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using next-generation sequencing have characterized the mutational landscape and identified the genetic drivers of DLBCL 7,10,11 . Several gene mutations including MYD88 L265P and CD79B mutations, NOTCH1 mutations, and TP53 mutations are independent risk factors related to poor prognosis in DLBCL patients 7,[10][11][12][13][14][15] . Additionally, recent studies have emphasized the prognostic role of the tumor microenvironment (TME) in DLBCL, and several biomarkers related to the TME have thus been identified [16][17][18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%